Identifying Early Carboniferous bimodal volcanic rocks and geochemical characteristics in the Atengtao Mountain, Yili Block (Chinese western Tianshan). (2nd February 2018) - Wang, Zuopeng; Li, Yongjun; Tong, Lili; Yang, Gaoxue; Ren, Pengfei; Wang, Ran; Li, Hai
Abstract : The Early Carboniferous bimodal volcanic rocks are firstly recognized in the Atengtao Mountain, Yili Block (Chinese Western Tianshan). The bimodal volcanic rocks are composed of dominant rhyolite and subordinate basaltic andesite. The SiO2 contents of basaltic andesites span a range of 52.08 to 60.44 wt.%, whereas those of the rhyolites range from 72.50 to 76.78 wt.%, showing a sharp gap between 60.44 and 72.50 wt.% for SiO2 content. Zircon U–Pb dating of rhyolitic sample yielded crystallization age of 340 ± 6 Ma, which is interpreted as the extrusive age of the bimodal volcanic rocks. Basaltic andesite samples belong to the calc‐alkaline series, whereas rhyolites are peraluminous. The basaltic andesite samples display enrichment in LREE ((La/Yb) N = 3.16–6.27), and nearly no obvious Eu anomalies (δEu = 0.86–1.21), with relative enrichment in large ion lithophile elements (Rb, K, Sr, U) and depletion in high field strength elements (Nb, Ta). Compared to the basaltic andesites, the rhyolites show enriched LREE patterns ((La/Yb) N = 7.05–9.27) and significantly negative Eu anomalies (δEu = 0.36–0.62), with remarkably negative Nb, Ta, P, Ti, and Sr anomalies, which is consistent with A‐type granites. The rhyolites have positive εHf( t ) values from 1.5 to 4.8 and TDM2 (Hf) values from 1, 036 to 1, 247 Ma. The basaltic andesites are interpreted as resulting from partial melting of an enriched lithospheric mantle source that was metasomatized by subduction‐related components, whereas the rhyolites were derived from basaltic melt‐induced reworking of Proterozoic juvenile crustal material. Based on our data, and taking into account the regional geology, a model of back‐arc setting was proposed for the Early Carboniferous formation of the bimodal volcanic rocks in the Atengtao Mountain. Therefore, we suggest that the volcanic rocks were likely induced by the northward subduction of the South Tianshan Ocean. The subduction resulted in opening of a back‐arc basin in Atengtao Mountain, leading to upwelling of mantle that had produced the basaltic andesites. Moreover, this process provided heat to remelt the crustal materials and form the rhyolites.